36.3k views
4 votes
A) laplace transform of 4t^2 sin 3t + e^-2t + t
b)......................... te^-2t cos 3t

1 Answer

6 votes

Answer:

a.L(s)=
(-24)(81-s^4)/((s^2+9)^4)+(1)/(s+2)+(1)/(s+1)

b.
L(s)=-(-s^2-4s+5)/((s^2+4s+13)^2)

Explanation:

We have to find the laplace transform of each function

a.
4t^2sin3t+e^(-2t)+t


L(t^nf(t))=(-1)^n(d^nF(s))/(ds^n)


L(t^n)=(n!)/(s^n+1)


L(e^(at))=(1)/(s-a)


L(sinat)=(a)/(s^2+a^2)


L(e^(at)cosbt)=(s-a)/((s-a)^2+b^2)

Apply the formula

Then we get


12(-1)^2(d^2((1)/(s^2+9)))/(ds^2)+(1)/(s+2)+(1)/(s+1)


(-24)(s^4+81+18s^2-2s^4-18s^2)/((s^2+9)^4)+(1)/(s+2)+(1)/(s+1)

L(s)=
(-24)(81-s^4)/((s^2+9)^4)+(1)/(s+2)+(1)/(s+1)

b.
te^(-2t)cos3t

f(t)=
e^(-2t)cos3t


F(s)=(s+2)/((s+2)^2+9)=(s+2)/(s^2+4s+13)


L(s)=-(dF(s))/(ds)=-(s^2+4s+13-(2s+4)(s+2))/((s^2+4s+13)^2)


L(s)=-(5-s^2-4s)/((s^2+4s+13)^2)

User Skeppet
by
4.6k points